Didaktiska stämmor om undervisande förskollärare - Linda Palla; Ann-Christine Vallberg-Roth (Educare)
We use didactic grounding to explore and develop knowledge regarding what might constitute a teaching preschool teacher. The research questions are 1) Which didactic components emerge in preschool teachers’ and managers’ written descriptions? and 2) How may these didactic components be interpreted and understood? In 2018, at the end of a 3-year-long project about teaching in preschool, we have analysed 160 written reflections by preschool teachers and managers from 10 Swedish municipalities through multi-vocal didactic modelling. Similar to previous research, this study indicates a linguistic shift as the preschool teachers and managers have embraced the concept of “teaching” and, with their written descriptions, fill the picture of a “teaching preschool teacher” with didactic content and meaning. The results highlight characteristic components that can be understood as preschool teachers’ didactic approaches, knowledge, and practice. These components include aspects such as awareness, presence, reflection, theoretical knowledge, goal-oriented planning, implementation, and follow-up.